Hydrocarbon Source Rock Potential of the Sinamar Formation, Muara Bungo, Jambi - Zajuli, Moh. Heri Hermiyanto; Panggabean, Hermes (Geological Agency, 2014)
DOI:Â 10.17014/ijog.v1i1.175The Oligocene Sinamar Formation consists of shale, claystone, mudstone, sandstone, conglomeratic sandstone, and intercalation of coal seams. The objective of study was to identify the hydrocarbon source rock potential of the Sinamar Formation based on geochemichal characteristics. The analyses were focused on fine sediments of the Sinamar Formation comprising shale, claystone, and mudstone. Primary data collected from the Sinamar Formation well and outcrops were analyzed according to TOC, pyrolisis analysis, and gas chromatography - mass spectometry of normal alkanes that include isoprenoids and sterane. The TOC value indicates a very well category. Based on TOC versus Pyrolysis Yields (PY) diagram, the shales of Sinamar Formation are included into oil prone source rock potential with good to excellent categories. Fine sediments of the Sinamar Formation tend to produce oil and gas originated from kerogen types I and III. The shales tend to generate oil than claystone and mudstone and therefore they are included into a potential source rock.Â